ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aims to determine the factor of the Current Ratio (CR), Debt To Equity Ratio (DER), Return on Equity (ROE), Retun on Assets (ROA), and net profit margin (NPM) of the company's stock price and the Real Estate category Property listed on the Indonesia Stock Exchange (IDX). The population is the entire Real Estate and Property companies in Indonesia Stock Exchange (IDX) the number of 49 companies and research over the period 2009 to 2011. Samples taken in this study is as much 44companie. The sampling technique used was purposive sampling. The analytical tool used in this study is multiple regression analysis. The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 32.9%. As for the test statistic F-test showed that, between CurrentRatio (CR), Debt To Equity Ratio (DER), Return on Equity (ROE) Return on Assets (ROA), and net profit margin (NPM) jointly affect the price stock. Hypothesis testing results show that there is positive Return On Equity (ROE) on stock prices. While to Current Ratio (CR), Debt To Equity Ratio (DER), Return on Assets (ROA), Net Profit Margin (NPM) shows that there is a negative effect on stock prices.Keywords : Current Ratio (CR), Debt To Equity Ratio (DER), Return On Equity (ROE), Return On Asset (ROA), Net Profit Margin (NPM), And Stock Price.